2017
DOI: 10.1098/rsta.2015.0390
|View full text |Cite
|
Sign up to set email alerts
|

D/H ratios of the inner Solar System

Abstract: The original hydrogen isotope (D/H) ratios of different planetary bodies may indicate where each body formed in the Solar System. However, geological and atmospheric processes can alter these ratios through time. Over the past few decades, D/H ratios in meteorites from Vesta and Mars, as well as from S- and C-type asteroids, have been measured. The aim of this article is to bring together all previously published data from these bodies, as well as the Earth, in order to determine the original D/H ratio for eac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(23 citation statements)
references
References 129 publications
(189 reference statements)
1
22
0
Order By: Relevance
“…In addition to the one ocean (≅1.5 × 10 21 kg) of water on Earth's surface, another several oceans' worth of hydrogen as OH and H 2 O are believed to reside in Earth's mantle including the transition zone (Bercovici & Karato, ; Genda, ; Hirschmann, ; Mottl et al, ). The average D/H ratio of this water is approximately 150 × 10 −6 (or − 37‰ in δD notation; Hallis, ). (Here following common usage, D refers to 2 H and H to 1 H; H 2 is of unspecified isotopic composition.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the one ocean (≅1.5 × 10 21 kg) of water on Earth's surface, another several oceans' worth of hydrogen as OH and H 2 O are believed to reside in Earth's mantle including the transition zone (Bercovici & Karato, ; Genda, ; Hirschmann, ; Mottl et al, ). The average D/H ratio of this water is approximately 150 × 10 −6 (or − 37‰ in δD notation; Hallis, ). (Here following common usage, D refers to 2 H and H to 1 H; H 2 is of unspecified isotopic composition.…”
Section: Introductionmentioning
confidence: 99%
“…The second is thought to represent the primordial martian mantle with a D/H ratio of 1.99 ± 0.02 × 10 −4 , which is enriched relative to VSMOW by a factor of 1.3 6 . Analyses of hydrous phases in martian meteorites and in-situ analyses of materials on the martian surface yield a wide range of D/H values that largely sit between these two endmembers 7 , 8 , so many previous studies have implicated mixing of these reservoirs and/or terrestrial contamination to explain the observed variations in D/H ratios. However, Mars lacks unambiguous evidence of once having Earth-style plate tectonics, and in the absence of plate tectonics, the crust acts as a physicochemical barrier between the atmosphere and mantle, hence it is a critical part of constraining any mixing model between the atmosphere and mantle reservoirs.…”
mentioning
confidence: 99%
“…However, exceptions occur with the recent discovery of the regolith breccia, NWA 7034 [3,4]. Martian meteorites are not only crucial for constraining the petrology of Mars but also for studying the paleoclimate history [5], Martian chronology [6], the origin of Martian water, and the habitability of Mars [7,8]. Such records are however challenging to constrain based on the convolution of information retained in meteoritic phases from the limited suite of Mars laboratory samples we have on Earth.…”
Section: Introductionmentioning
confidence: 99%